Diagnostics of Human Middle-East Respiratory Syndrome - L. F. Stovba; V. N. Lebedev; A. A. Petrov; V. S. Kulish; S. V. Borisevich (Проблемы особо опасных инфекций, 2014)
Middle-East respiratory syndrome is a human disease caused by a new coronavirus. In December, 2012 WHO published draft regulatory document on diagnostics of the virus. It was recommended to use two methods of disease diagnostics - two-phase reverse-transcription real-time PCR and enzyme immunoassay. The first phase of the PCR-diagnostics should include reverse-transcription real-time PCR targeted on the genome fragment upwards of upE. The second (control) PCR-test may be alternatively targeted within the bonds of the genome, its target being non-crisscross with upE gene. It should include sequencing of, at least, a segment of one of the viral genomes and comparative analysis of the obtained sequence along with the like ones deposited in the GenBank. Enzyme immunoassay is retrospectively used for virus-specific antibody detection in convalescents’ blood sera. Examined are the key specifications of the methods for the detection of ethiological agent or specific antibodies to it, and WHO methodological recommendations in case of Middle-East respiratory syndrome diagnostics.